Molecular insight into affinities of drugs and their metabolites to lipid bilayers - Paloncýová, Markéta; Berka, Karel; Otyepka, Michal (The journal of physical chemistry. B, 2013)
The penetration properties of drug-like molecules on human cell membranes are crucial for understanding the metabolism of xenobiotics and overall drug distribution in the human body. Here, we analyze partitioning of substrates of cytochrome P450s (caffeine, chlorzoxazone, coumarin, ibuprofen, and debrisoquine) and their metabolites (paraxanthine, 6-hydroxychlorzoxazone, 7-hydroxycoumarin, 3-hydroxyibuprofen, and 4-hydroxydebrisoquine) on two model membranes: dioleoylphosphatidylcholine (DOPC) and palmitoyloleoylphophatidylglycerol (POPG). We calculated the free energy profiles of these molecules and the distribution coefficients on the model membranes. The drugs were usually located deeper in the membrane than the corresponding metabolites and also had a higher affinity to the membranes. Moreover, the behavior of the molecules on the membranes differed, as they seemed to have a higher affinity to the DOPC membrane than to POPG, implying they have different modes of action in human (mostly PC) and bacterial (mostly PG) cells. As the xenobiotics need to pass through lipid membranes on their way through the body and the effect of some drugs might depend on their accumulation on membranes, we believe that detailed information of penetration phenomenon is important for understanding the overall metabolism of xenobiotics.
Keywords: buněčná membrána; Lipid Bilayers; léčivé přípravky; chlorzoxazon; Humans; ibuprofen; Pharmaceutical Preparations; Caffeine; fosfatidylcholiny; fosfatidylglyceroly; termodynamika; kumariny; lidé; Xenobiotics; Phosphatidylglycerols; debrisochin; simulace molekulární dynamiky; Cytochrome P-450 Enzyme System; lipidové dvojvrstvy; Thermodynamics; Coumarins; Molecular Dynamics Simulation; Ibuprofen; xenobiotika; kofein; Debrisoquin; Phosphatidylcholines; Cell Membrane; Chlorzoxazone; systém (enzymů) cytochromů P-450